2011
DOI: 10.25011/cim.v34i1.14908
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between lipoprotein(a) and coronary artery disease, as well as its variable nature following myocardial infarction

Abstract: Turkeye relationship between lipoprotein(a) and coronary artery disease, as well as its variable nature following myocardial infarction AbstractPurpose: e present study aimed to investigate the relationship between the severity of coronary artery disease (CAD) and level of Lipoprotein (LP)(a).Methods: e study included 52 CAD patients and a control group consisting of 38 individuals. e patients were classi ed into three groups based on the clinical form of CAD (stable angina pectoris, SAP, unstable angina pecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
(36 reference statements)
1
6
0
1
Order By: Relevance
“…Another interesting thing is the level of Lp (a) also reflects the degree of severity and is associated with the number of coronary arteries that terlibat 7,8,9 . Other studies have also shown consistent results in which the levels of Lp (a) in patients with three vessels disease two times higher than patients with one or two blood vessels involved 2,10,11,12 . Research also shows that levels of Lp (a) increases in patients with acute coronary syndrome and higher in patients with significant coronary lesions (≥ 50%) but had a weak correlation (r = 0.106) with the degree of severity of lesion 13 .…”
supporting
confidence: 60%
“…Another interesting thing is the level of Lp (a) also reflects the degree of severity and is associated with the number of coronary arteries that terlibat 7,8,9 . Other studies have also shown consistent results in which the levels of Lp (a) in patients with three vessels disease two times higher than patients with one or two blood vessels involved 2,10,11,12 . Research also shows that levels of Lp (a) increases in patients with acute coronary syndrome and higher in patients with significant coronary lesions (≥ 50%) but had a weak correlation (r = 0.106) with the degree of severity of lesion 13 .…”
supporting
confidence: 60%
“…The findings are in agreement with those of which Gaziano et al (2010) Ahyana et al (2014), who noted health behavior related with the age, and marital status. However, compared to the study of Ornek et al (2011) (Gaziano et al, 2010). A history of prior smoking was more strongly associated with MI in men compared to that in women (Anand et al, 2008), also it was reported that a woman controls smoking easier than a man (NHLBI, 2014 (Damman et al, 2013).…”
Section: Most Of the Patients In This Studymentioning
confidence: 84%
“…Total cholesterol was positively associated with ischemic heart disease mortality at all blood pressure levels (Zodpey, Shrikhande, Negandhi, Ughade, & Joshi, 2015). Moreover, high cholesterol levels are estimated to cause 56% of ischemic heart disease Worldwide (Gaziano et al, 2010 (Ornek et al, 2011).…”
Section: Most Of the Patients In This Studymentioning
confidence: 98%
“…5 The wide range of Lp(a) in this study may be due to the varying severity of MI, as it has been shown to correlate with the size of the necrotic area. 6,7 Due to the limitation of available clinical details, this correlation could not be analysed in this study.…”
Section: Discussionmentioning
confidence: 99%